Mathematical modelling, simulation and emulation of the electro-mechanical system, flywheel-gear train-engine - Guerrero Otoya, Luis Daladier; Zárate Luna, Paola (I+ T+ C- Research, Technology and Science, 2019)
This paper presents the mathematical modelling, simulation and emulation of the electro-mechanical system, flywheel-gear train-engine. Continuous time modelling was performed in the state space, then the most representative transfer function was selected and discretized using the zero pole mapping method to finally emulate the system using the Arduino Uno electronic platform. Both in the simulation performed in Matlab as in the Arduino emulation, similar behaviors were obtained with a gain of 0.68.